WAKTU PEMBERIAN RETARDAN PADA BEBERAPA VARIETAS KACANG TANAH (Arachys hipogaea L.) - Sri Mursiani Arifah (Jurnal Gamma, 2012)
WAKTU PEMBERIAN RETARDAN PADA BEBERAPAVARIETAS KACANG TANAH (Arachys hipogaea L.)Sri Mursiani ArifahStaf Pengajar, Jurusan Agroteknologi, Fakutas Pertanian PeternakanUniversitas Muhammadiyah MalangEmail: sri_mursiani@umm.ac.idABSTRACTHigh and low plant peanuts directly affects the interest that has been fertilized, strike the ground and become pithy pods and production levels. In general, peanuts entered high generative phase ranges from 60-70 cm, depending on the varieties used, the alternative solution of the problem when using retardants effective time of administration to certain varieties of peanuts.Purpose of the study to determine the timing of the effective retardants in some varieties of peanuts. Conduct of research using randomized block design arranged in factorial. Factor I, consisting of three levels of administration time and factor II consisted of four varieties of varieties, each repeated three times.Observations show that there has interaction between timing of retardan giving and peanut varieries in all research variable.Conclusions of this study is the effective time of each delivery retardants varieties at the age of 2 weeks and no difference in the response of each variety on the provision of retardants on the age of 2 weeks, but different compared with the control and administration retardants at the age of 4 weeks. Giving retardants at the age of 2 weeks tingga plants obtained from four varieties of peanuts ranges from 34.55 - 35.21 cm with a weight range of the pithy pods per plot 1232.23 - 1233.98 kg per plot.Key words: retardants, and varieties